Nurse's Effective Communication Ability to Patient's Safety in Hospitals - Loetfia Dwi Rahariyani; Nikmatul Fadilah; Yessy Dessy Arna; Jenie Palupi (Health Notions, 2022)
Communication errors in the treatment process will have an impact on the safety and security of patients in the hospital. The emergence of wrong perceptions among health professionals can result in conflict or harm to the patient, leading to lawsuits. The purpose of this study was to identify the nurse's ability to communicate effectively the SBAR technique on patient safety in the hospital. The study used cross-sectional design. Subjects were 225 nurses that they worked at medical surgical ward of 2 hospitals in East Java, selected using cluster sampling technique in July 2019. Independent variable was effective communication-SBAR (Situation, Background, Assessment, Recommendation) technique and dependent variable was patients safety goals. Ordinal regression test was used to analyze the influence of effective communication-SBAR on patient safety goals. The Most of the nurses had received training in effective communication and patient safety. The majority of nurses had good skills on SBAR-based effective communication, but more than half of nurses had low patient safety goals. The conclusion is: effective communication of SBAR has no significant effect on patient safety objectives. This is due to other factors that can affect the implementation of effective communication for patient safety. Keywords: effective communication; patient safety; hospital